An analysis of cross-linguistic influence in the production of L2 lexical bundles among ESL learners - Abd Razak, Harniza; Ahamad Shah, Mohamed Ismail (2015)
This paper presents an analysis of cross-linguistic influence in the production of L2 lexical bundles among English as a Second Language (ESL) learners. The data for the analysis were collected from 40 ESL students’ term papers from Universiti Teknologi Mara Terengganu. The frequency of lexical bundles found in the essays was calculated, the types of the bundles were sorted according to their categories and the factors contributing to the use lexical bundles were identified. In research on language teaching and learning, the term cross-linguistic influence describes the conscious and unconscious process of transferring the first language to the target language. This cross-linguistic influence creates the problem of learnability as it causes interlingual and intralingual errors. In this study, the students were found to produce inaccurate lexical bundles which were caused by interlingual transfer, intralingual transfer and also improper acquisition of lexical bundles. The findings regarding cross-linguistic influence in L2 lexical bundles generally show that the L2 students had unconsciously and automatically applied the bundles due to L1 transfer, L2 overgeneralization and also improper acquisition of lexical bundles. These three factors contributed to misapplication of lexical bundles in a real context. An important pedagogical implication of the study is that lexical bundles should be exposed or taught to students in formal classroom teaching in order to help students produce more understandable and quality writing.